Chronic cervicitis and treatment by electric surgery - Achard, Arturo (2015)
In our opinion this work culminated in the treatment of chronic cervicitis, with the support of an important casuistry, indicating therein the importance we attach to the electrical surgery, and especially electric conization of the cervix. In support of our preference for this technique a number of clinical considerations they are made, and anatomical and pathological deduced from the evolution of the operated sick, and the detailed study of histological sections of excised cones